Ultrastructural and thermal analyses reveal novel insights into low-temperature survival mechanisms of hydrated seeds of Poaceae species from alpine regions - Jiajin Li; Ganesh K. Jaganathan; Xuemin Han; Baolin Liu (Plant Diversity, 2025)
Global warming leads to snow cover loss in the alpine ecosystem, exposing seeds to extreme diurnal temperature fluctuations during the growing season. The risk of freezing increases as seeds have increased moisture content. Studying the survival mechanisms of seeds at low temperatures can help analyze changes in alpine meadow populations and target conservation efforts. Here, we used three species of Poaceae as a model to understand freezing stress. Fully imbibed Elymus dahuricus, Festuca elata, and Lolium multiflorum seeds were subjected to programmed cooling at fast and slow rates (−1.0/0.05 °C/min) and then assessed for survival. Differential Scanning Calorimetry was used to analyze thermal transitions during cooling. HE-stained paraffin sections and a Transmission Electron Microscope were employed to observe internal morphology and ultrastructural changes. E. dahuricus seeds exhibited greater tolerance to low temperatures than those of the other two species, with an LT50 of approximately −20 °C for both cooling rates and maintained relatively intact ultrastructure. The observed the low-temperature exotherm (LTE) correlated with seed survival, with viability decreasing extensively below LTE. Fast cooling caused fewer changes to seed morphology and ultrastructure than slow cooling, suggesting that the primary survival mechanism during fast cooling is freezing avoidance through supercooling. Seeds exhibited greater freeze tolerance under slow than fast cooling, primarily by migrating intracellular water to extracellular spaces where it froze, causing considerable damage to cell ultrastructure and forming apparent cavities in some seeds.